Strengthening MSME Adaptation Strategies through the Integration of Digital Marketing, Creative Innovation, and Technological Capabilities in Facing Business Environment Uncertainty - Sutrisno; Nugrahini Susantinah Wisnujati; Dewa Oka Suparwata (PT. LITERASI SAINS NUSANTARA, 2026)
This study aims to analyze the strengthening of adaptation strategies for Micro, Small, and Medium Enterprises (MSMEs) through the integration of digital marketing, creative innovation, and technological capabilities in responding to business environment uncertainty. The study employs a qualitative approach using a literature review method, where data were obtained from various scientific publications and credible sources through searches on Google Scholar and official websites of relevant institutions within the period of 1991–2026. From an initial pool of 50 articles, a rigorous selection process was conducted based on relevance, quality, and contribution to the research topic, resulting in 27 articles for further analysis using descriptive analysis techniques. The findings indicate that the integration of digital marketing enables expanded market access and improved customer interaction, while creative innovation plays a role in generating product differentiation and business flexibility. Technological capabilities are also proven to enhance operational efficiency and MSME readiness in facing change. However, the implementation of these three aspects still encounters various challenges, such as low digital literacy, limited access to technology, and suboptimal policy support. Therefore, integrated efforts are required through strengthening human resource capacity, providing access to technology and financing, and fostering collaboration among stakeholders to sustainably enhance MSME resilience and competitiveness.